2011
DOI: 10.1158/1078-0432.ccr-11-0224
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Are Independent Predictors of Outcome in Diffuse Large B-Cell Lymphoma Patients Treated with R-CHOP

Abstract: Purpose Diffuse large B-cell lymphoma (DLBCL) heterogeneity has prompted investigations for new biomarkers that can accurately predict survival. A previously reported 6-gene model combined with the international prognostic index (IPI) could predict patients’ outcome. However, even these predictors are not capable of unambiguously identifying outcome, suggesting that additional biomarkers might improve their predictive power. Experimental Design We studied expression of 11 microRNAs that had previously been r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
101
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 46 publications
3
101
0
Order By: Relevance
“…17 We previously demonstrated that miR-181a has a prognostic value in DLBCL, by establishing a positive correlation between high endogenous miR-181a expression in tumor biopsies and longer survival in patients undergoing rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone therapy. 18 Beyond this prognostic value, we asked whether distinct miR-181a expression contributes to different DLBCL patient survival. Indeed, several studies demonstrated that miR-181a regulates key cell-survival proteins and oncogenic signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…17 We previously demonstrated that miR-181a has a prognostic value in DLBCL, by establishing a positive correlation between high endogenous miR-181a expression in tumor biopsies and longer survival in patients undergoing rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone therapy. 18 Beyond this prognostic value, we asked whether distinct miR-181a expression contributes to different DLBCL patient survival. Indeed, several studies demonstrated that miR-181a regulates key cell-survival proteins and oncogenic signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we selected miR-18a as a candidate for this plasma assay. MiR-18a also has been reported to show altered expression in various malignant diseases [30,31]. In breast cancer, the relationship with ERalpha, identified as a direct target of miR18a, has been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…That said, these mice, or indeed mice that over-express AICDA, do not develop overt lymphoma (Muto et al, 2006). Interestingly, AICDA is also targeted by MIR181 (de Yebenes et al, 2008), an independent prognostic indicator of survival in R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisolone) treated DLBCL patients (Alencar et al, 2011).…”
Section: Mir155mentioning
confidence: 99%